Community-Engaged Learning Within the Medical Curriculum: Evaluating Learning Outcomes and Implementation Challenges - Rahul Pandit; Rens L. Essers; Helena J. M. Pennings (International Medical Education)
Community engaged learning (CEL) is a teaching methodology which aims to bridge the gap between academia and society by collaborating on community-based projects. Inspired by theories of experiential learning and social constructivism, CEL celebrates learning by doing and is a rather novel teaching methodology within the predominantly theoretical bachelor medical curriculum. Despite CEL’s potential benefits, its implementation faces significant challenges. Here, we investigated how students, accustomed to traditional academic teaching, learn during CEL-infused courses, specifically studying student perception of their learning and identifying the various facilitators and barriers to learning during CEL. The study conducted at Utrecht University’s Faculty of Medicine included second-year medical students participating in a newly introduced CEL course. Using thematic analysis, the study analyzed students’ written reflections collected before and after completion of the course. CEL contributed to developing valuable competencies like empathy, leadership, and communication skills, which go beyond the realm of textbook and classroom-based knowledge. The study further identified key barriers and facilitators, both at personal and organizational levels influencing learning outcome of students. Based on these data, several recommendations have been formulated for all involved parties (students, academic institutions, community partners) which could contribute towards a sustainable embedding of CEL.